Effects of Psychological Interventions on Postpartum Depression, Anxiety and Infants' Weight in Primipara Women - ahmad ahmadi; sayeh sadat moosavi sahebalzamani; farah Ghavami; yaaghob shafiee; ali fathi ashtiani (Zanjan University of Medical Sciences and Health Services, 2014)
Background and Objectives: Anxiety and postpartum depression are devastating conditions that affect both pregnant women and their infants. The current study aimed to evaluate effect of psychological interventions on postpartum depression, anxiety and infants' weight in primipara women referred to Baghiatallah and Najmiyeh hospitals in 2013. Materials and Methods: In this randomized controlled trial, out of 534 pregnant women who were in their last trimester of pregnancy, 135 at risk women were selected. The participants were randomly assigned to the experimental or control groups. The intervention program composed of eight educational and cognitive-behavioral sessions. Individuals in the control group received usual care. The symptoms of anxiety and depression were assessed using the Beck Anxiety Inventory, the Edinburgh Postpartum Depression Scale and the Beck Depression Inventory. Infantschr('39') birth weights were also measured. Results: There were no significant differences between the two groups regarding baseline measurements. The anxiety and depressive symptoms scores were reduced significantly in the intervention group (p<0/05). There were no changes in the mean of birth weight in both groups after the intervention. Conclusion: Findings suggested that psychological interventions could reduce symptoms of emotional problems in postpartum period.